Gender Variations of Physiolocical and Psychological Stress Among Police Officers - Martin Gächter; David A. Savage; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2009)
This paper analyses the effect of gender on reported and perceived levels of stress through examination of both the physical and psychological indicators. It may be interesting to work with police data due to high stress levels among police officers and the fact that the work environment is male dominant (females are a minority). In our study we not only explore gender differences, but also whether job and private environmental factors such as effective cooperation between units, a higher trust in the work partner, a higher level of work-life-balance and home stability, and a higher level of interactional fairness, affect female and male officers differently. Using multivariate regression analysis of police officers we find that female officers are significantly more likely to report suffering from physical stress indicators than their male counterparts while no gender differences are observable in regards to psychological stress. Moreover, a higher level of trust and cooperation, and a higher level of interactional fairness at work are not able to absorb physical stress among female, while these factors have a strong impact on male officers. On the other hand, for both, female and male officers, work-life balance and stability at home have the tendency of reducing physical stress.
Keywords: I10; I12; I31; J24; J81; Z13; 330; Gender; Stress; Police Officers; Burnout; Work-life Balance; Justice